2023
DOI: 10.3390/nano13111731
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Hydrothermal Synthesis of Cu2ZnSnS4 Nanoparticles as an Efficient Visible Light Photocatalyst for the Degradation of Congo Red Azo Dye

Rodrigo Henríquez,
Paula Salazar Nogales,
Paula Grez Moreno
et al.

Abstract: A hydrothermal method was successfully employed to synthesize kesterite Cu2ZnSnS4 (CZTS) nanoparticles. X-ray diffraction (XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), field-emission scanning electron microscopy (FE-SEM), energy-dispersive X-ray spectroscopy (EDS), transmission electron microscopy (TEM), and optical ultraviolet-visible (UV-vis) spectroscopy were used for characterization of structural, chemical, morphological, and optical properties. XRD results confirmed that a nanocrysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 66 publications
0
8
1
Order By: Relevance
“…The rate constants were calculated to be 0.0233, 0.0156, 0.0113, and 0.0081 min –1 for the CR initial concentrations of 20, 40, 60, and 100 mg L –1 , respectively. The time-dependent absorption spectra (Figure d) show a characteristic peak at 510 nm due to the n-π* transition of the azo group . The progressive decrease of the absorption peak with illumination time confirms the visible light-facilitated degradation of CR, which could be seen from the inset image of Figure d displaying the decolorization of CR with time.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…The rate constants were calculated to be 0.0233, 0.0156, 0.0113, and 0.0081 min –1 for the CR initial concentrations of 20, 40, 60, and 100 mg L –1 , respectively. The time-dependent absorption spectra (Figure d) show a characteristic peak at 510 nm due to the n-π* transition of the azo group . The progressive decrease of the absorption peak with illumination time confirms the visible light-facilitated degradation of CR, which could be seen from the inset image of Figure d displaying the decolorization of CR with time.…”
Section: Resultsmentioning
confidence: 56%
“…Figure S4 (Supporting Information) shows the excellent stability of CNCS-0.15 for five successive cycles with less than a 5% decrease from its initial activity. For a comparative analysis, Table S3 compiles the degradation ability of CR using other binary/ternary catalysts which signifies the potential of CNCS-0.15 for real-time remediation of dyes and other pollutants. ,, …”
Section: Resultsmentioning
confidence: 99%
“…CZTSe-NPs were characterized by different techniques that provided information about their structural and chemical composition and morphological, optical, and optoelectronic properties. These characterizations were performed as previously reported by our group [33] (see also Supplementary Material SI).…”
Section: Characterization Of the Cztse-npsmentioning
confidence: 99%
“…To establish the photodegradation of dye and the regeneration of the CZTSe-NP photocatalyst, studies were carried out employing a 50 mL solution of 0.04 mM Congo red azo dye, to which 35 mg of Cu 2 ZnSnSe 4 nanoparticles were added. The studies were performed as previously reported by our group [33] (see also Supplementary Material SI).…”
Section: Photodegradation Of Cr Azo Dye and Photocatalyst Regeneratio...mentioning
confidence: 99%
See 1 more Smart Citation